Parathyroid Carcinoma: Analysis of Patient Characteristics and Outcomes in a Retrospective Review of Eight Cases seen in a Single Center - Shahar, Shamira; Lim, Kim Piow; Mohamad, Masni (Journal of the ASEAN Federation of Endocrine Societies, 2019)
Eight cases of parathyroid carcinoma were identified (8 females; median age 45 years, range 28-72). Half of whom were diagnosed preoperatively. Hypercalcemic symptoms were seen in 87.5% of the patients and the main complication was nephrolithiasis. At presentation, the median calcium was 3.675 mmol/L, median phosphate of 0.68 mmol/L, median intact parathyroid hormone (iPTH) was 211 pmol/L. Five patients had regional nodes metastasis and 1 had distant metastasis to the lungs. Parathyroid gland invasion to adjacent structures was seen in 62.5% of cases while another 62.5% showed capsular or vascular infiltration on histology with median tumour size of 3.2 cm. Recurrent hypercalcemia occurred in 50% of the patients with median time of recurrence of 21 months. In this case series, we found that patients with severe hypercalcemia and high iPTH also exhibited a high index suspicion of PC.